2002
DOI: 10.1002/jmv.2196
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to respiratory syncytial virus infection in inbred mice

Abstract: Differences in the severity of respiratory syncytial virus (RSV)-induced lower respiratory disease in infants have been attributed to multiple environmental and genetic factors. To identify the genetic factor(s) influencing RSV susceptibility, we examined RSV infection in eight inbred mouse strains. Lung RSV titers differed significantly between mouse strains: the RSV titers were 15-fold higher in AKR/J (permissive) mice compared with C57BL/6J (resistant) mice at 4 days after inoculation. This strain-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 62 publications
7
81
0
Order By: Relevance
“…2A, significant weight loss was observed for unimmunized animals or mice immunized either with UV-RSV or WT-BCG, as well as BCG-OVA (data not shown). These data are consistent with previous studies indicating that naive mice challenged with RSV can show significant weight loss as early as 24 h after infection (35)(36)(37). In sharp contrast, mice immunized with either BCG-N or BCG-M2 showed no significant weight loss after RSV challenge, similarly to uninfected mice (Fig.…”
Section: Resultssupporting
confidence: 93%
“…2A, significant weight loss was observed for unimmunized animals or mice immunized either with UV-RSV or WT-BCG, as well as BCG-OVA (data not shown). These data are consistent with previous studies indicating that naive mice challenged with RSV can show significant weight loss as early as 24 h after infection (35)(36)(37). In sharp contrast, mice immunized with either BCG-N or BCG-M2 showed no significant weight loss after RSV challenge, similarly to uninfected mice (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In models of RSV disease, mice with different genetic backgrounds respond to RSV with strain-specific cytokines and pathophysiological responses (7,8). Our laboratory has previously shown that the up-regulation of IL-13 in RSV-infected BALB/c exacerbates mucus production, airway hyperreactivity, and airway inflammation (9 -11), whereas others have indicated that the age of infection can influence the production of IL-13 (12).…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…Because of this, the laboratory mouse has been the experimental model of choice to study pathogenesis of infection, including innate and acquired host defense mechanisms. Inbred mouse strains differ significantly in their degree of susceptibility to infection with various human bacterial (eg, Mycobacterium tuberculosis, 15,16 Salmonella enterica, 17 Streptococcus pyogenes, 18 Streptococcus pneumoniae 19 ), fungal (eg, Histoplasma capsulatum, 20 Aspergillus fumigatus 21 ), protozoan (eg, Leishmania major, 22 Plasmodium berghei, 23 Plasmodium chabaudi 24 ), helminthic (eg, Schistosoma mansoni 25,26 ) as well as viral (eg, respiratory syncytial virus 27,28 ) pathogens. This attribute has been exploited to identify novel loci influencing resistance/susceptibility to infection and to provide new insight on host mechanisms involved in response to those pathogens that ultimately affect the onset, progression, and outcome of the infection.…”
mentioning
confidence: 99%